Who’s Afraid of Islamic Family Law?: Dealing with Shari‘a-based Family Law Systems in the Netherlands - Sportel, Iris (Religion & gender, 2017)
In the Netherlands, where views of Muslims and Islamic family law are highly politicised, the application of Islamic family laws by Dutch courts is a topic of heated political debate. Especially polygamy and unilateral divorce by men (talaq) are thought to have a strongly negative impact on the position of Muslim women in the family. In order to assess the gendered impact of Islamic family laws in a European context, this article takes a closer look at Dutch state courts’ decisions. It asks how the application of Islamic family laws can be understood against the background of Dutch political discourses on Islam, family law and women’s rights. While in public and political debates, Islamic family laws are frequently thought to be women-unfriendly, this article shows that the encounter between Islamic family laws and Dutch law often has severe impact on the position of Muslim men living in the Netherlands.